O najstarszych polskich przekładach literatury słowackiej - Spyrka, Lucyna (Przekłady Literatur Słowiańskich, 2018)
About the Oldest Polish Translations of Slovak Literature Based on J. Jarniewicz’s concept of two types of translator’s attitude: legislator and ambassador, the article concentrates on the reasons behind the oldest Polish translations of Slovak literature: a folk song, part of J. Rostworowski’s novel Zamek na Czorsztynie, a novel by J. Kalinčiak Reštavrácia translated by P. Stalmach and a drama Matka by J. Gregor Tajovský translated by F. Gwiżdż, showing the circumstances of their appearance and the attitudes of their translators. KEY WORDS: translation, history, Slovak literature, Polish literature, translator